The Finnish Allergy Programme 2008-2018 - scientific rationale and practical implementation - Haahtela, Tari (Asia Pacific Association of Allergy, Asthma and Clinical Immunology, 2012)
There are no nationwide, comprehensive public health programmes on allergic disorders with set goals and systematic follow-up. The Finnish initiative is based on the idea that the so called allergy epidemic in modern, urban societies is caused by inadequately developed or broken tolerance. The immune system is not trained to make the difference between danger and non-danger (allergy) or the difference between self and non-self (autoimmune diseases). The immune dysfunction leads to inappropriate inflammatory responses and clinical symptoms. The 10-year implementation programme is aimed to reduce burden of allergies both at the individual and societal levels. This is done by increasing both immunological and psychological tolerance and changing attitudes to support health instead of medicalising common and mild allergy symptoms. Severe forms of allergy are in special focus, e.g. asthma attacks are prevented proactively by improving disease control with the help of guided self-management. Networking of allergy experts with primary care doctors and nurses as well with pharmacists is the key for effective implementation. Non-governmental organizations have started a campaign to increase allergy awareness and knowledge among patients and general public. It is time to act, when allergic individuals are becoming a majority of Western populations and their numbers are in rapid increase worldwide. The first results of the Finnish Programme indicate that allergy burden can be reduced with relatively simple means.